2011
DOI: 10.1007/s10344-011-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Responses of red deer (Cervus elaphus) to regular disturbance by hill walkers

Abstract: Disturbance to wildlife from human recreational activities is increasing as remote areas become accessible to greater numbers of people. We used Global Positioning System tracking collars to monitor the movements of red deer (Cervus elaphus) stags (n=8) in a herd whose feeding grounds lie close to a popular walking track in the Highlands of Scotland. The track is used by around 20,000 walkers per year and is busiest in summer and at weekends. In a 2-year study, the locations of collared deer were recorded at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 39 publications
(34 reference statements)
4
43
1
1
Order By: Relevance
“…Further, he reported that hunting generally increases flight responses even if such behaviour can be mitigated by habituation. Contrariwise, Sibbald et al (2011) observed that red deer might alter their behaviour and diet composition, as a result of disturbance from human recreational activities, even when they were habituated to regular disturbance within their home range. However, most of studies concerning the response of wildlife to human activities deal with the effect of diurnal disturbance.…”
Section: Discussionmentioning
confidence: 97%
“…Further, he reported that hunting generally increases flight responses even if such behaviour can be mitigated by habituation. Contrariwise, Sibbald et al (2011) observed that red deer might alter their behaviour and diet composition, as a result of disturbance from human recreational activities, even when they were habituated to regular disturbance within their home range. However, most of studies concerning the response of wildlife to human activities deal with the effect of diurnal disturbance.…”
Section: Discussionmentioning
confidence: 97%
“…In winter, by contrast, disturbance appeared to increase the amount of grass in the diet. However, the balance between recreation and hunting as sources of disturbance to red deer changes between summer and winter, with the winter months seeing both a reduction in the number of walkers using the tracks (Sibbald et al 2011) and an increase in hunting activity (Bullock et al 1999). Although the spatio-temporal nature of hunting activity is unpredictable, hunting is not normally carried out in areas that are frequently visited by the general public (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not expect habitat effects on diet composition, since the plantderived material in faeces were just as likely to have come from some other habitat type as the one in which the faeces were found. Low-digestibility grass species and heather can take as long as 30 to 40 h to pass though the alimentary tract in deer (Milne et al 1978) and deer can be expected to travel around 2 km per day in winter and as far as 5 km per day in late spring in that region (Sibbald et al 2001), so that Mean percentage of GSHR (grass, sedges, herbs and rushes) in the diet of red deer in spring, estimated from faeces collected from disturbed (black bars) and less-disturbed (white bars) areas in grassland, heather moorland and woodland sites, with SE bars the likelihood of movement between habitat types within a day was fairly high. It is therefore not easy to explain the interactions between effects of disturbance and habitat type on diet composition.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that damage increases when deer are restricted in their movements, either by snow or by human disturbance (Van de Veen 1973, Maizeret andBallon 1990). Red deer seem sensitive to disturbance (Sunde et al 2009, Sibbald et al 2011, Jarnemo and Wikenros 2014 and bark-stripping level has already been related to human activity (Petrak 1998, Ligot et al 2013. The intensity of damage thus likely depends both on the availability and the quality of day-time security cover (Borkowski and Ukalski 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Forageincreasing measures may thus also be used to attract ('pull') deer to sites where their presence is acceptable. As disturbance can cause red deer to leave sites (Sunde et al 2009, Sibbald et al 2011, Jarnemo and Wikenros 2014, an additional step could be to divert ('push') deer from sites where damage is undesirable (Cromsigt et al 2013). This combination of forage-increasing measures and disturbance actions-so called 'push-pull strategies' (Cook et al 2007)-merits further study.…”
Section: Recommendations For Management and Researchmentioning
confidence: 99%